2018
DOI: 10.1159/000492387
|View full text |Cite
|
Sign up to set email alerts
|

Increased Energy Expenditure, Lipolysis and Hyperinsulinemia Confer Resistance to Central Obesity and Type 2 Diabetes in Mice Lacking Alpha2α-Adrenoceptors

Abstract: The alpha2A-adrenoceptors (α2A-ARs) are Gi-coupled receptors, which prejunctionally inhibit the release of norepinephrine (NE) and epinephrine (Epi), and postjunctionally inhibit insulin secretion and lipolysis. We have earlier shown that α2A–/– mice display sympathetic hyperactivity, hyperinsulinemia and improved glucose tolerance. Here we employed α2A–/– mice and placed the mice on a high-fat diet (HFD) to test the hypothesis that lack of α2A-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 63 publications
2
4
0
Order By: Relevance
“…The beneficial effects of swimming training were also observed in CON‐EXE rats for the glucose plasma levels and GSIS, while no difference was found for glucose sensitivity, indicating that the effect exercise on GSIS may be independent of changes in pancreatic islets sensitivity to glucose. Moreover, previous studies reported that physical activity also modulates the GSIS due to its effect on adrenergic pathways in pancreatic islets from lean and obese mice models, an event that could also be present in our study . The reduced GSIS in exercised groups corroborate with previous reports that also used swimming training as exercise protocol .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The beneficial effects of swimming training were also observed in CON‐EXE rats for the glucose plasma levels and GSIS, while no difference was found for glucose sensitivity, indicating that the effect exercise on GSIS may be independent of changes in pancreatic islets sensitivity to glucose. Moreover, previous studies reported that physical activity also modulates the GSIS due to its effect on adrenergic pathways in pancreatic islets from lean and obese mice models, an event that could also be present in our study . The reduced GSIS in exercised groups corroborate with previous reports that also used swimming training as exercise protocol .…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, previous studies reported that physical activity also modulates the GSIS due to its effect on adrenergic pathways in pancreatic islets from lean and obese mice models, an event that could also be present in our study. 36,37 The reduced GSIS in exercised groups corroborate with previous reports that also used swimming training as exercise protocol. 33,38 However, it has been also demonstrated that physical activity increases GSIS in rats submitted to intense treadmill training, while in moderate protocol no effect is observed.…”
Section: Discussionsupporting
confidence: 88%
“…Peripheral and central (in raphe pallidus) injections of ␣ 2 -AR agonists were recently shown to inhibit BAT thermogenesis in rats (96), indicating that ␣ 2 -AR exhibit inhibitory control over BAT thermogenesis. Emerging evidence further suggests that an interplay between the relative expression or affinities of various ARs is not only important for the thermogenic outcome in BAT, but may also influence browning of WAT depots in rodents (131). In contrast to rodents, human adipocytes predominantly express ␤ 1 -and ␤ 2 -ARs, which have also been shown to play a role in human BAT activity (115,148).…”
Section: Sympathetic Nervous System-mediated Regulation Of Brown and Beige Fatmentioning
confidence: 99%
“…Mouse models with increased energy expenditure typically have a lean phenotype, with decreased weight gain in fat‐rich diets. Examples are knockout of the Maf1 regulator of Pol III transcription (Willis et al ), treatment with OXPHOS uncouplers (Goldgof et al ; Kalinovitch and Shabalina ; Suzuki et al, ) and genetic modifications that increase sympatho‐adrenal tone (Ruohonen et al ). Thus, our expectation was that AOX would also have this effect in mice.…”
Section: Introductionmentioning
confidence: 99%